Magnetic Nanoparticles Decorated with Gold Nanoclusters–Applications in Cancer Theranostics - Marijus Pleckaitis; Vitalijus Karabanovas; Greta Butkiene; Jonas Venius; Marius Burkanas; Giedre Grinciene; Arunas Jagminas; Ricardas Rotomskis (Advanced Materials Interfaces, 2023)
Abstract Nanomedicine presents exciting new opportunities for the detection and treatment of cancer. Current cancer imaging methods and treatment approaches in clinics frequently fall short of entirely curing cancer and can have severe side effects. Theranostic nanoparticles, however, have the potential to revolutionize effective cancer treatment and early cancer detection. The objective of this study is to show how magnetic iron oxide nanoparticles and photoluminescent gold nanoclusters (MN‐AuNCs) may be combined effectively to produce bimodal imaging nanoparticles that possess magnetic and optical properties and can be used for both magnetic resonance imaging and optical biopsy. These findings demonstrate that MN‐AuNCs, when exposed to visible light, also have the capability to produce singlet oxygen, which is necessary for photodynamic therapy of cancer. In addition, it shows that they are non‐toxic, accumulate inside the cells, and cause cell death during exposure to visible light. The creation of these MN‐AuNCs offers a novel remedy for the current shortcomings in cancer diagnosis and treatment. Since they have both therapeutic and imaging capabilities, MN‐AuNCs have the potential to improve patient outcomes while lowering the risk of negative side effects.